2018
DOI: 10.3390/polym10050512
|View full text |Cite
|
Sign up to set email alerts
|

Study of theThermo-/pH-Sensitivity of Stereo-Controlled Poly(N-isopropylacrylamide-co-IAM) Copolymers via RAFT Polymerization

Abstract: Abstract:In this work, a smart copolymer, Poly(nipam-co-IAM) was synthesized by copolymerization of N-isopropylacrylamide (nipam) and itaconamic acid (IAM) through reversible addition-fragmentation chain-transfer (RAFT) polymerization. Poly(nipam-co-IAM) has been studied previously synthesized via radical polymerization without stereo-control, and this work used cumyl dithiobenzoate and Ytterbium(III) trifluoromethanesulfonate as RAFT and stereo-control agents, respectively. The stereo-control result in this w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 37 publications
0
8
0
Order By: Relevance
“…Other kinds of applications were the combination of those polymers to generate macroscopic composites to be used as pressure sensors and thermal switch, microwave responsive devices, and chemo-mechanical actuators [16,17,18]. In recent years, a series of copolymers based on PNIPAM were synthesized, demonstrating the versatility of this thermosensitive polymer for the development of new materials [19,20,21,22,23]. Hsiao et al [24] demonstrated that it is possible to grow PANI from the alkyl amine (R-NH 2 ) groups of chitosan producing another kind of NIR absorbing hydrogel.…”
Section: Introductionmentioning
confidence: 99%
“…Other kinds of applications were the combination of those polymers to generate macroscopic composites to be used as pressure sensors and thermal switch, microwave responsive devices, and chemo-mechanical actuators [16,17,18]. In recent years, a series of copolymers based on PNIPAM were synthesized, demonstrating the versatility of this thermosensitive polymer for the development of new materials [19,20,21,22,23]. Hsiao et al [24] demonstrated that it is possible to grow PANI from the alkyl amine (R-NH 2 ) groups of chitosan producing another kind of NIR absorbing hydrogel.…”
Section: Introductionmentioning
confidence: 99%
“…Even though they react sluggishly in FRP conditions, ATRP and RAFT have been successful at obtaining copolymers containing itaconic acid derivatives 24 . For example, pH‐ and temperature‐sensitive random copolymers of NIPAAm and itaconamic acid were obtained by RAFT in Rwei's group 240,241 . RAFT polymerization of vinyl monomers derived from renewable sources, for example aminoacids, carbohydrates, lignin, plant oils, has been recently reviewed 242 …”
Section: Toward “Greener” Msr Polymersmentioning
confidence: 99%
“…[ 151 ] In the field of stimulus‐responsive polymers, copolymerization of itaconamic acid and N ‐isopropylamine (NIPAM) via RAFT in was reported, which led pH‐ and thermoresponsive polymers. [ 152 ] Fluorescent copolymers were obtained from styrene and itaconic acid by photo‐initiated RAFT with a fluorophore‐bearing RAFT agent. [ 153 ] These copolymers self‐assembled into organic nanoparticles and could be loaded with the anti‐cancer drug cisplatin.…”
Section: Controlled Radical Polymerization Of Itaconic Acid and Its Dmentioning
confidence: 99%